Transcriptome Analysis of B Cell Immune Functions in Periodontitis: Mucosal Tissue Responses to the Oral Microbiome in Aging - Ebersole, Jeffrey L.; Kirakodu, Sreenatha S.; Novak, M. John; Orraca, Luis; Martinez, Janis Gonzalez; Cunningham, Larry L.; Thomas, Mark V.; Stromberg, Arnold; Pandruvada, Subramanya N.; Gonzalez, Octavio A. (Frontiers in Immunology, 2016)
Evidence has shown activation of T and B cells in gingival tissues in experimental models and in humans diagnosed with periodontitis. The results of this adaptive immune response are noted both locally and systemically with antigenic specificity for an array of oral bacteria, including periodontopathic species, e.g. Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans. It has been recognized through epidemiological studies and clinical observations that the prevalence of periodontitis increases with age. This report describes our studies evaluating gingival tissue transcriptomes in humans and specifically exploiting the use of a nonhuman primate model of naturally-occurring periodontitis to delineate gingival mucosal tissue gene expression profiles focusing on cells/genes critical for development of humoral adaptive immune responses. Patterns of B cell and plasmacyte genes were altered in aging healthy gingival tissues. Substantial increases in a large number of genes reflecting antigen-dependent activation, B cell activation, B cell proliferation, and B cell differentiation/maturation were observed in periodontitis in adults and aged animals. Finally, evaluation of the relationship of these gene expression patterns with those of various tissue destructive molecules (MMP2, MMP9, CTSK, TNF, and RANKL) showed a greater frequency of positive correlations in healthy tissues versus periodontitis tissues, with only MMP9 correlations similar between the two tissue types. These results are consistent with B cell response activities in healthy tissues potentially contributing to muting the effects of the tissue destructive biomolecules, whereas with periodontitis this relationship is adversely affected and enabling a progression of tissue destructive events.